2003
DOI: 10.1046/j.1523-1747.2003.12321.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Events Are Involved in Acne Lesion Initiation

Abstract: The earliest subclinical acne "lesion" is a microcomedone, of which hyperproliferation of the follicular epithelium is a characteristic feature. Inflammatory cells have been observed at the periphery of these "lesions". This study investigated whether inflammatory events occur pre or post hyperproliferative changes. Cellular, vascular, and proliferative markers were examined by immunohistochemical techniques on biopsies of clinically normal follicles from uninvolved skin and early inflamed lesions from acne pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
326
2
31

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 431 publications
(382 citation statements)
references
References 31 publications
(28 reference statements)
11
326
2
31
Order By: Relevance
“…149 Immunohistochemical studies of earliest subclinical acne lesions demonstrated an increase of IL-1α labelling in all layers of interfollicular and perifollicular epidermis and down the follicle wall of uninvolved skin of acne patients compared to controls. 150 Down the follicular wall only labelling in the infrainfundibular basal cells increased, whereas labelling in the suprabasal layers of the infrainfundibulum and all layers of the acroinfundibulum did not differ in intensity in uninvolved skin of acne patients and early inflamed lesions. 150 Within the dermis IL1-α labelling presented a discrete cellassociated immunoreactivity with the majority of positive cells located perifollicularly, whereas in normal skin only a small number of dermal cells expressed IL-1α.…”
Section: Interleukin-1α Network In Keratinocytesmentioning
confidence: 75%
See 1 more Smart Citation
“…149 Immunohistochemical studies of earliest subclinical acne lesions demonstrated an increase of IL-1α labelling in all layers of interfollicular and perifollicular epidermis and down the follicle wall of uninvolved skin of acne patients compared to controls. 150 Down the follicular wall only labelling in the infrainfundibular basal cells increased, whereas labelling in the suprabasal layers of the infrainfundibulum and all layers of the acroinfundibulum did not differ in intensity in uninvolved skin of acne patients and early inflamed lesions. 150 Within the dermis IL1-α labelling presented a discrete cellassociated immunoreactivity with the majority of positive cells located perifollicularly, whereas in normal skin only a small number of dermal cells expressed IL-1α.…”
Section: Interleukin-1α Network In Keratinocytesmentioning
confidence: 75%
“…159 It is most likely that increased IL-1α activity has initiated the upregulation of vascular adhesion molecules, ICAM-1, E-selectin and VCAM-1 and the cellular migration of CD4 + -T-cells and macrophages found in uninvolved and early inflammatory lesions of acne patients. 150 It is conceivable that androgen-dependent FGFR2-mediated release of IL-1α by infrainfundibular keratinocytes is the primary stimulus leading to comedogenesis, a state of secretory keratinocyte activation inducing the perifollicular infiltration by T-cells and macrophages. A further link between IL-1α and initiation of the immune response is the fact that, activated IL-1 receptor associated kinases (IRAKs) are critically involved in the IL-1 receptor/Toll-like receptor-mediated signal transduction processes that regulate cellular innate and adaptive immune responses.…”
Section: Ser252trp-fgfr2-mutation and Comedogenesismentioning
confidence: 99%
“…65 MC-1R expression has been shown to be upregulated by proinflammatory signals. 66,67 As proinflammatory cytokines are upregulated in acne lesions, 68 sebocytes may respond to these signals with increased MC-1R expression, thereby generating a negative feedback mechanism for α-MSH which exerts direct anti-inflammatory actions, i.e., inhibition of IL-1-mediated IL-8 secretion. 64,65 Cannabinoid receptors (CR), which mediate the psychopharmacological action of marijuana have been not only localised in the central and peripheral nervous system but also in human skin.…”
Section: Effects Of Hormones On Sebaceous Gland Cellsmentioning
confidence: 99%
“…Recent studies support the latter hypothesis by demonstrating that an increase in IL-1 activity occurs before the hyperproliferation around uninvolved follicles and this triggers the activation of the keratinocytes. 68,75 Expression profiling of acne-involved and uninvolved skin from cells and of E-selectin by perisebaceous venules. Facial skin from acne patients is characterised by rich innervation, by increased numbers of substance P-containing nerves and mast cells, and by strong expression of neutral endopeptidase in sebaceous glands and E-selectin in venules around sebaceous glands, compared with normal skin.…”
Section: Inflammation Sebaceous Gland Cells and Acnementioning
confidence: 99%
See 1 more Smart Citation